2015
DOI: 10.1039/c5ra01267h
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance of graphene directly and locally grown on bulk nickel substrate by laser irradiation

Abstract: ARTICLE This journal is ARTICLE This journal isWe report the anticorrosion capability of graphene directly and locally grown on bulk nickel substrate by a high power laser beam at room temperature. The anticorrosive performance of the locally laser-grown graphene on Ni, together with Ni covered graphene transferred from CVD method and bare Ni, was investigated by electrochemical measurements and immersion tests. The corrosion rate evaluated from potentiodynamic polarizations was 4.5 times lower than that for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…with those of the bare Ni, implying that the graphene/Ni samples effectively resisted the HCl and KOH corrosive environments. 23,24 In a 1 M KOH solution, the corrosion current density of a grown graphene sample was smaller than that of bare Ni, indicating that graphene has superior corrosion resistance in a basic environment. The anticorrosion mechanism of the graphene/Ni sample may have been due to the impermeability of the graphene.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…with those of the bare Ni, implying that the graphene/Ni samples effectively resisted the HCl and KOH corrosive environments. 23,24 In a 1 M KOH solution, the corrosion current density of a grown graphene sample was smaller than that of bare Ni, indicating that graphene has superior corrosion resistance in a basic environment. The anticorrosion mechanism of the graphene/Ni sample may have been due to the impermeability of the graphene.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…11 Ni/ 0.5 M HCl Corrosion rate of graphene coated Ni was 4.5 times lower than bare Ni. [110] 12 Carbon steel) 3.5% NaCl Corrosion rate for graphene coated carbon steel was much lesser (0.05 mm per year) as compared to the non-coated carbon steel (0.09 mm per year). [111] 13 Stainless steel, Cu, Ni, and CuNi…”
Section: Chemically Modified Go As Aqueous Phase Corrosion Inhibitorsmentioning
confidence: 94%
“…Later studies confirmed that graphene coatings grown directly on a metal outperform mechanically transferred graphene (Mišković-Stanković et al, 2014). Besides the damage inflicted to graphene by the mechanical transfer, the problem with transferred graphene coatings is the weak adhesion to the target metal surface, which, over time, causes delamination of the coating (Ye et al, 2015). This is partially due to the intrinsic surface roughness of the target subject; the smoother the surface, the stronger the adhesion with the graphene sheet.…”
Section: Transfer Onto Target Metalsmentioning
confidence: 97%